2016
DOI: 10.1093/ageing/afw201
|View full text |Cite
|
Sign up to set email alerts
|

Increased orthogeriatrician involvement in hip fracture care and its impact on mortality in England

Abstract: in the context of initiatives to improve hip fracture care, we identified statistically significant and robust associations between increased orthogeriatrician hours per patient and reduced 30-day mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 12 publications
1
28
0
2
Order By: Relevance
“…Now only 78% of the patients above 70 receive orthogeriatric management during admission, which is low compared to the 2016 NHFD in which 89% of the patients above 60 years of age received orthogeriatric management [ 4 ]. A study with NHFD data also demonstrated that an increase of orthogeriatric treatment hours per patient was associated with a 3.4% relative risk reduction of mortality [ 38 ]. In the DHFA, only 23% of the patients is treated on a special ward with high orthogeriatrician hours per patient.…”
Section: Discussionmentioning
confidence: 99%
“…Now only 78% of the patients above 70 receive orthogeriatric management during admission, which is low compared to the 2016 NHFD in which 89% of the patients above 60 years of age received orthogeriatric management [ 4 ]. A study with NHFD data also demonstrated that an increase of orthogeriatric treatment hours per patient was associated with a 3.4% relative risk reduction of mortality [ 38 ]. In the DHFA, only 23% of the patients is treated on a special ward with high orthogeriatrician hours per patient.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognised that comprehensive geriatric assessment is crucial in the management of patients with hip fractures 47. A higher number of orthogeriatrician contact hours per patient has been shown to reduce 30-day mortality from a fractured hip 48. Irrespective of specific injury, there is a high prevalence of cognitive impairment and polypharmacy among older trauma patients, and complications such as delirium and acute kidney injury are common 49.…”
Section: Where Should This Man Be Admitted?mentioning
confidence: 99%
“…62 Furthermore, the risk of in-hospital death depends on the length of time spent in hospital, which in turn depends on the presence (or absence) of early discharge policies. 3 The risk of death may also depend on where patients undergo treatment, 37,38 because of between-hospital differences in quality of care, 20 intensity of care, 63 clinical pathways, 42,64 and care standards. 20,65 [Insert Figure 1 and Table 1 here]…”
Section: Dependency Graphmentioning
confidence: 99%
“…Clinical pathways bring attention to hip fracture patients and their prioritization on operating room lists, which facilitates early access to surgery and is associated with better outcomes. 42,64 Clinical pathway Treatment in hospitals with lower care intensity leads to death. 63 Care intensity…”
Section: Structurementioning
confidence: 99%